Knowledge of obstetric danger signs and its associated factors among husbands residing in the Raya Kobo district, Ethiopia - Derbew, Jemal; Yesuf, Adem; Mihrete, Abebe; Abdallah, Amira; Mohammed, Abdurehman; Sirage, Nurye; Molla, Bogale (Frontiers in Public Health, 2024)
BackgroundThe term “danger signs” refers to any symptoms or indicators that suggest a pregnant woman may be at risk during pregnancy. Mothers are often burdened with responsibilities, and the majority of them do not even receive treatment for potential complications, which can ultimately lead to the loss of their lives. This situation highlights the barriers that prevent them from being properly prepared for potential risks. In Ethiopia, various studies have been conducted on male involvement in pregnancy, but none have assessed knowledge of obstetric danger signs (ODS). While a few studies have focused on husbands’ knowledge of obstetric danger signs, there is still variation in the variables examined.ObjectivesThe objective of the study was to assess the level of knowledge about obstetrical danger signs and the associated factors among husbands whose wives were pregnant and gave birth within the last 12 months in the Raya Kobo district, North Wollo, Amara Ethiopia, in 2023.MethodsA community-based cross-sectional study was conducted from 29 April to 30 May 2023 in the Raya Kobo district. A multi-stage stratified random sampling technique was used to select 626 samples. The data were analyzed using SPSS version 26.00 statistical software. Independent variables with a p-value of ≤0.25 in the bivariate analysis were considered candidates for multivariate analysis, and a p-value of ≤0.05 was considered statistically significant.ResultsRegarding knowledge about obstetric danger signs, 46.3% (95% CI: (42.6 to 50.3%)) of the respondents had good knowledge. The variables significantly associated with knowledge about obstetric danger signs included husbands who attended secondary school (adjusted odds ratio (AOR) = 4.77, 95% CI, (1.42–16.04)), those living in urban areas (AOR = 3.00, 95%CI = (1.59, 7.57)), those with an average monthly income between 3,001 and 5,000 birr (AOR = 3.35, 95% CI = (1.58, 7.12)), and those with more than five children (AOR = 0.15, 95% CI = (0.05–0.46)).Conclusion and recommendationsThe knowledge of obstetric danger signs among husbands in the Raya Kobo district was limited. The educational status of the husband, average family income, residence, and number of children were significantly associated with the husbands’ knowledge of obstetric danger signs. Therefore, these findings highlight the importance of addressing knowledge gaps through targeted educational programs aimed at improving awareness of obstetric danger signs.